2023
DOI: 10.3390/su15032319
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Corporate Digital Responsibility: A Digital Technology Development Perspective

Abstract: Managers and scholars require an appropriate conceptualization, as well as reliable and valid measures of corporate digital responsibility (CDR), to better understand and tackle issues involving CDR. Therefore, by combining insights from extant research on corporate responsibility in the digital realm, this article proposes to distinguish CDR into corporate digitized responsibility and corporate digitalized responsibility. Specifically, corporate digitized responsibility includes unbiased data acquisition, dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…This finding highlights the crucial role of business leaders and employees in shaping the organization's CDR strategy. Specifically, our results in Table 2 ( Model 3 ) uncover that managers who have mentors with international experience exhibit a higher propensity to embrace digital security and consumer protection features in their businesses (Cheng & Zhang, 2023). Furthermore, the presence of business leaders with family relationships in other countries positively influences the utilization of digital tools for analyzing and researching business questions (Lobschat et al, 2021).…”
Section: Discussion and Implicationmentioning
confidence: 96%
See 2 more Smart Citations
“…This finding highlights the crucial role of business leaders and employees in shaping the organization's CDR strategy. Specifically, our results in Table 2 ( Model 3 ) uncover that managers who have mentors with international experience exhibit a higher propensity to embrace digital security and consumer protection features in their businesses (Cheng & Zhang, 2023). Furthermore, the presence of business leaders with family relationships in other countries positively influences the utilization of digital tools for analyzing and researching business questions (Lobschat et al, 2021).…”
Section: Discussion and Implicationmentioning
confidence: 96%
“…Within this dynamic context, cybersecurity, artificial intelligence (AI), and governance are critical concerns demanding attention. In the corporate realm, business leaders are pivotal agents accountable for steering their organizations, making them key figures in CDR at an individual level (Cheng & Zhang, 2023). Simultaneously, employees play a significant part in driving CDR initiatives forward.…”
Section: The Impact Of Human Capital On Corporate Digital Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the digital economy on economic development is multi-dimensional. At the micro level, digital transformation can significantly improve the information-processing capability of enterprises, promote the flow of information elements within enterprises (Shen and Yuan, 2020), improve the innovation capability of enterprises (Manesh et al, 2020), promote EGS performance (Cheng and Zhang, 2023;Zhong et al, 2023), optimize organizational structures, and enhance production and operation processes (Hess et al, 2016). Boland et al (2007) studied the influence of DT on innovation and found that enterprise-distributed technology has strong "technical penetration, " which can meet the needs of the complex business-ecology relationship.…”
Section: The Economic Effects Of Digital Technologymentioning
confidence: 99%
“…Therefore, the key to implementing the rural revitalization strategy is to capitalize on the advantages of the digital economy. Developed countries worldwide are also deeply applying digital technology to actual production and life [8][9]. Digital technology is fully integrated with agricultural production and rural life, which can not only enhance agricultural production capacity and increase income for farmers but also give rise to more advanced digital agricultural technology on this basis, accelerating the countryside's modernization process [10][11].…”
Section: Introductionmentioning
confidence: 99%